Pengaruh Konsentrasi Rootone F terhadap Induksi Akar dan Tunas Stek Pucuk Kopi Arabika (Coffea arabica) - Fauzia Dona; Gustian Gustian; Wulan Kumala Sari (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2023)
Coffee is a plantation commodity which important to increase its production, such as by vegetative propagation i.e., shoot cuttings that stimulated by Plant Growth Regulators (PGR). The research was on the effect of Rootone F concentrations on roots and shoots induction of Arabica coffee (Coffea arabica) shoot cuttings, it was carried out at the smallholder coffee plantation Solok Radjo in Aie Dingin Village, Lembah Gumanti District, Solok Regency on April until August 2022. The objectives of this study were to determine the growth response of Arabica coffee shoot cuttings on the induction of the roots and shoots, and to determine the best concentration of Rootone F PGR on the growth of it. This study was designed by a Completely Randomized Design (CRD) with 6 concentrations of Rootone F, namely: 0, 200, 400, 600, 800, and 1000 ppm. The observed variables were percentage of live cuttings, first shoots emergence, longest root and shoot, number of roots and shoots, and fresh weight of roots. The obtained data were analyzed of variance at the 5% level and if it was significantly different continued by Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that there was a shoot cuttings growth response of Arabica coffee on the variable of percentage of living cuttings, first shoots emergence, longest root and shoot, and fresh weight of roots, except on the variable number of roots and shoots. The best concentration of Rootone F PGR on the roots and shoots induction of Arabica coffee shoot cuttings in supporting its growth was 400 ppm.